Soon : Stories - Durban, Pam (Book collections on Project MUSE., 2015)
"Pam Durban's new collection of stories explores the myriad ways people lose, find, and hold on to one another. When all else fails her characters--science, religion, family, self--the powerful act of storytelling itself keeps their broken lives together and fosters hope. Each story in this rewarding and multifaceted collection introduces people who yearn for better lives and find themselves entangled in the hopes and dreams that heal and bind us all. The title story in Soon--chosen by John Updike for The Best American Short Stories of the Century anthology--follows two generations of a family whose lives are driven by the "patient and brutal need that people called hope, which. formed from your present life a future where you would be healed or loved." In "The Jap Room," winner of the 2008 Goodheart Prize, a woman tries to help her husband, a World War II veteran, finally come home. "Rowing to Darien" introduces a famous English actress as she rows away from her husband's rice plantation. In "Hush" a gravely ill man encounters himself in the darkness of Kentucky's iconic Mammoth Cave. An adopted child waits for his mother to come back for him in "Birth Mother," and, in "Forward, Elsewhere, Out," a mother must come to terms with her adolescent son's sexuality. The stories in this collection deftly broach universal themes of love, loss, and the redemptive power of storytelling. Durban's writing has been praised for its depth and mastery of characterization, its ability to persuade readers that the lives of the people in her stories are true, that their troubles and pleasures are real enough to matter. The nuanced and artfully rendered cast in this collection wrestles with the big questions that face us all--Why are we here? How are we to live? What matters most? The thirteen stories in Soon have appeared in earlier forms in Atlanta Magazine, Indiana Review, Georgia Review, Carolina Quarterly, Idaho Review, Southern Review, Kenyon Review, Shenandoah, Five Points, High Five: An Anthology of Fiction from 10 Years of Five Points, New Stories from the South: The Year's Best, Best American Short Stories, and Best American Short Stories of the Century. The collection includes a foreword from novelist and short story writer Mary Hood, winner of the Flannery O'Connor Prize, Townsend Prize, and Lillian Smith Award"--